ANALYSIS OF HUMAN RESOURCE QUALITY AS INFLUENCED BY TRANSFORMATIONAL LEADERSHIP, WORK DISCIPLINE, AND WORK ENVIRONMENT MEDIATED BY MOTIVATION AT RAFLESIA SMK IN DEPOK CITY - Amril; Fajar Cahyo Utomo; Harry Indra Tjahyo (Krisnadwipayana International Journal of Management Studies, 2025)
To determine and analyze the effect of transformational leadership, work discipline, work environment on motivation and also motivation on the quality of human resources at SMK Raflesia Depok. The method used in this research is quantitative descriptive method. the sample used was 40 respondents. The analytical tool used is Partial Least Square (PLS) regression with the help of SmartPLS 3 software. The findings of the research conducted are Transformational Leadership has a significant effect on Motivation. Work Discipline has a significant effect on Motivation. The work environment has no significant effect on motivation. Motivation has a significant effect on the quality of human resources.